Export processing in the Caribbean : lessons from four case studies (ECLAC SantiagoCL, 1994)
Reviews case studies of four countries - the Dominican Republic, Jamaica, Saint Lucia and Trinidad Tobago - and assesses tthe contribution that export processing has made to industrial development in each.
DC